Vigilance and foraging behaviour of female caribou in relation to predation risk - Bøving, Pernille S.; Post, Eric (Rangifer, 1997)
Behaviour of female caribou (Rangifer tarandus) was investigated during the calving season on ranges in Alaska and West Greenland with the purpose of determining whether investment in vigilance behaviour differed between areas with and without natural predators of caribou. Female caribou in Alaska foraged in larger groups, displayed a higher rate of vigilance during feeding, spent less time feeding and, when lying, more often adopted a vigilant posture (with head up) than did female caribou in West Greenland. Moreover, a predation-vulnerable posture of lying down flat was observed in West Greenland but not in Alaska. Within Alaska, females with calves spent more time searching the environment than did those without calves. Finally, the amount of time individuals spent searching declined more gradually with group size in Alaska than in West Greenland, suggesting that what caribou perceive as a predator-safe threshold differs in the two areas. These results indicate that caribou, like several other species of ungulates, show behavioural adaptations to the risk of prédation which are relaxed when this risk is reduced.